The Contributions of Green Education to Reshaping the Human–Place Relationship social Work in the Field of Environment and Population as a Model A Study Conducted on a Sample of Students from the Faculty of Arts, Al-Swain (Al-Farooq Journal of Sciences, 2026)
Green education is an educational approach that seeks to integrate the principles of sustainability and environmental protection into the educational process by raising students’ awareness of environmental issues and encouraging them to adopt responsible behaviors toward natural resources and the environment. The environmental field is considered one of the most important areas studied within Social Work departments at Libyan universities, with the aim of promoting optimal human behavior toward the environment through professional interventions with individuals, groups, and communities. Such interventions help foster a sense of belonging to the place in which people live, enabling them to become active contributors to the development of their communities.This study aims to identify the contributions of green education in reshaping the positive relationship between human beings and their environment. The study employed the descriptive research method and utilized a questionnaire as the primary data collection tool, based on a purposive sampling technique.The findings revealed several important results. Most notably, the concept of green education has not yet received adequate attention or application, and Libyan universities still need to further institutionalize green education as an educational strategy. The study also found that green education serves as an effective means of building a strong relationship between people and their environment and strengthening individuals’ sense of belonging to their surroundings. Furthermore, social work in the fields of environment and population requires further development in terms of curricula and professional practice mechanisms.
Keywords: Green Education, Human Being, Place, Social Work in the Field of Environment and Population.